Innovation in Digital Thesis Supervision Systems Using the Design Thingking Method - Anggreyni Cristine Putricia Br. Surbakti; Vika Oktaviani Silaen; Evta Indra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The thesis supervision process represents a critical academic milestone for undergraduate students; however, in many Indonesian higher education institutions, it continues to operate conventionally and inefficiently due to fragmented communication, unstructured revision management, and a lack of organized inter-session support. This study designs and evaluates the BimbOl mobile application prototype as a digital thesis supervision support system using the Design Thinking methodology through five sequential stages: empathize, define, ideate, prototype, and test. A preliminary survey of 57 respondents (45 students and 12 lecturers) identified four dominant barriers: difficulty in scheduling coordination (73.1% of students), unstructured revision management (57.8% of students), absence of proactive notifications (57.9% of students), and loss of inter-session discussion context (53.3% of students). The BimbOl prototype integrates six core features across 30 interactive screens, encompassing collaborative scheduling, digital revision markup, automated notifications, a progress dashboard, structured revision history, and a four-mode AI Consultation feature as an independent inter-session support tool not found in comparable systems. Usability evaluation using the System Usability Scale (SUS) involved 15 respondents (12 students and 3 lecturers) and yielded a combined score of 80.8, surpassing the Grade A threshold (80.3), confirming Excellent/Acceptable usability. The mean student score of 77.9 (Good/Acceptable) and the mean lecturer score of 90.0 (Excellent/Best Imaginable) confirm that the design is effective across both user groups. Unlike prior studies that addressed thesis supervision digitalization through isolated features or interface-level redesigns, this study contributes a unified, human-centered mobile supervision ecosystem that simultaneously resolves scheduling, revision tracking, notification, and AI-assisted inter-session consultation, a combination not previously documented in the Indonesian higher education context, thereby providing an empirical and design foundation for next-generation thesis supervision systems.